Alterations in the baroreceptor-heart rate reflex in conscious inbred polydipsic (STR/N) mice - Chu, C P; Cui, B R; Kannan, H; Qiu, D L (Physiological research, 2015)
STR/N is an inbred strain of mice which is known to exhibit extreme polydipsia and polyuria. We previously found central administration of angiotensin II enhanced cardiovascular responses in STR/N mice than normal mice, suggesting that STR/N mice might exhibit different cardiovascular responses. Therefore, in this study, we investigated daily mean arterial blood pressure and heart rate, and changes in the baroreceptor-heart rate reflex in conscious STR/N mice and control (ICR) mice. We found that variability in daily mean arterial blood pressure and heart rate was significantly larger in STR/N mice than in ICR mice (p<0.05). There was a stronger response to phenylephrine (PE) in STR/N mice than in ICR mice. For baroreceptor reflex sensitivity, in the rapid response period, the slopes of PE and sodium nitroprusside (SNP) were more negative in STR/N mice than in ICR mice. In the later period, the slopes of PE and SNP were negatively correlated between heart rate and blood pressure in ICR mice, but their slopes were positively correlated in STR/N mice. These results indicated that STR/N mice exhibited the different cardiovascular responses than ICR mice, suggesting that the dysfunction of baroreceptor reflex happened in conscious STR/N mice.
Keywords: Mice, Inbred ICR; Pressoreceptors; Baroreflex; baroreflex; krevní tlak; vazokonstriktory; mužské pohlaví; Mice; Heart Rate; srdeční frekvence; nitroprusid; Phenylephrine; zvířata; Blood Pressure; myši inbrední ICR; Nitroprusside; fenylefrin; vazodilatancia; Vasodilator Agents; polydipsie; myši; Vasoconstrictor Agents; Polydipsia; presoreceptory; Male; Animals